Attitude and Perception of B.Ed. Teacher Trainees and Faculties Inclusion of Sex Education in Secondary Schools by Colleges: - (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The aim is to study Attitude B.Ed. Teacher Trainees and Faculties Inclusion of sex education in secondary schools by colleges and perception of B.Ed. Teacher Trainees and Faculties Inclusion of sex education in secondary schools by colleges. Sex education is a lifelong cycle of building a strong sexual wellbeing foundation through the acquisition of information and the formation of character, relationship and closeness perspectives, convictions and qualities. The privileges of the whole youngster, and all kids, to endurance, protection, improvement and participation are at the focal point of all parts of the school and its encompassing education network. The finding of the study revealed that Teacher’s Trainees and faculties of B.Ed. colleges teaching in senior secondary schools have favourable attitude towards sex education.